The Protective Effect of Transplanting Liver Cells into the Mesentery on the Rescue of Acute Liver Failure after Massive Hepatectomy - Sadahiko Kita (Cell Transplantation, 2016)
Postoperative liver failure is one of the most critical complications following extensive hepatectomy. Although transplantation of allogeneic hepatocytes is an attractive therapy for posthepatectomy liver failure, transplanting cells via the portal veins typically causes portal vein embolization. The embolization by transplanted cells would be lethal in patients who have undergone massive hepatectomy. Thus, transplant surgeons need to select extrahepatic sites as transplant sites to prevent portal vein embolization. We aimed to investigate the mechanism of how liver cells transplanted into the mesentery protect recipient rats from acute liver failure after massive hepatectomy. We induced posthepatectomy liver failure by 90% hepatectomy in rats. Liver cells harvested from rat livers were transplanted into the mesenteries of hepatectomized rats. Twenty percent of the harvested cells, which consisted of hepatocytes and nonparenchymal cells, were transplanted into each recipient. The survival rate improved significantly in the liver cell transplantation group compared to the control group 7 days after hepatectomy (69 vs. 7%). Histological findings of the transplantation site, in vivo imaging system study findings, quantitative polymerase chain reaction assays of the transplanted cells, and serum albumin measurements of transplanted Nagase analbuminemic rats showed rapid deterioration of viable transplanted cells. Although viable transplanted cells deteriorated in the transplanted site, histological findings and an adenosine-5′-triphosphate (ATP) assay showed that the transplanted cells had a protective effect on the remaining livers. These results indicated that the paracrine effects of transplanted liver cells had therapeutic effects. The same protective effects were observed in the hepatocyte transplantation group, but not in the liver nonparenchymal cell transplantation group. Therefore, this effect on the remnant liver was mainly due to the hepatocytes among the transplanted liver cells. We demonstrated that transplanted liver cells protect the remnant liver from severe damage after massive hepatectomy.